Contesting middle-class civility: place-based collective identity in Hong Kong's Occupy Mongkok. (4th July 2018) - Yuen, Samson
Abstract: The global wave of popular protests since 2011 has highlighted the importance of place to contentious politics. Focusing on Hong Kong's Umbrella Movement, this article analyzes how place, when dramatized by the practice of protest camping, shapes collective identity formation and contestation. By examining the Mongkok protest camp, I argue that the symbolic meanings being attributed to the place have shaped a collective identity distinctive from other local protests. This place-based collective identity was constituted by two dimensions: a tactical dimension that advocated militant actions against the police and counter-protesters; and an associational dimension that sought to identify with the grassroots in political activism. While its formation helped to galvanize protesters' solidarity at the early stage of the movement, the two dimensions gradually generated intensive conflicts, which eventually weakened solidarity and the movement claims.